ChemInform Abstract: Combining Gold and Photoredox Catalysis: Visible Light‐Mediated Oxy‐ and Aminoarylation of Alkenes. Issue 38 (30th August 2013) - Sahoo, Basudev; Hopkinson, Matthew N.; Glorius, Frank
Abstract The novel title dual‐catalytic system gives access to a wide range of different arylated heterocyclic compounds.